Ravel the decadent : memory, sublimation, and desire - Puri, Michael J. (Oxford University Press, 2011)
"The music of Maurice Ravel (1875-1937), beloved by musicians and audiences since its debut, has been a difficult topic for scholars. The traditional stylistic categories of impressionism, symbolism, and neoclassicism, while relevant, have offered too little purchase on this fascinating but enigmatic work. In Ravel the Decadent, author Michael Puri provides an innovative and productive solution by locating the aesthetic origins of this music in the French Decadence and demonstrating the extension of this influence across the length of his oeuvre. From an array of Decadent topics Puri selects three--memory, sublimation, and desire--and uses them to delineate the content of this music, pinpoint its overlap with contemporary cultural discourse, and link it to its biographical context, as well as to create new methods altogether for the analysis and interpretation of music."--From publisher's description.